Rujukan Hukum Islam: Dalil-dalil Muttafaq dan Mukhtalaf - Sabri, Muhammad Rifal; Zulfan; Erman; Fauzi, Muhammad (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This article outlines the sources of law in Islam and the legal evidences in Islam, whether they are agreed upon (Muttafaq) or disputed (Mukhtalif). As followers of a religion, we should adhere to the laws reflected in its teachings, just as Islam also has rules and laws that its followers are obligated to observe. The sources of law in Islam are the Qur'an and the Sunnah, which are the word of Allah and the revelations of the Prophet, forming the foundation of Islamic teachings.The author employs a qualitative method, with the type of research used being library research. The reason for choosing this title is to examine the primary sources of law in Islam and to assess the validity (hujjah) of each legal provision in Islam.The results of this study show that understanding these two sources of law is crucial because they are interrelated in explaining the legal provisions applicable in Islam. Therefore, having a correct understanding of both should be a top priority, as errors in understanding them can undermine the validity of the legal sources themselves. By understanding the Qur'an and Hadith, we will gain legal guidance in accordance with the teachings of Sharia and the Sunnah of Prophet Muhammad (peace be upon him).